2015
DOI: 10.1111/jsm.13013
|View full text |Cite
|
Sign up to set email alerts
|

A Urologist's Guide to Ingredients Found in Top-Selling Nutraceuticals for Men's Sexual Health

Abstract: Introduction Use of supplements is common among men seeking urologic evaluation for sexual health matters. With a dizzying array of formulations available and little regulation on the dosage, purity, or ingredients found in these products, the health effects of nutraceuticals are often confusing to patients and medical practitioners alike. Aim In this review, we set out to concisely summarize the data on ingredients found wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 88 publications
0
24
0
2
Order By: Relevance
“…Prior research has similarly found evidence of social inequities in the burden these products pose, with two U.S. nationally representative studies finding lower-income adults more likely than their wealthier peers to use dietary supplements for weight loss (Pillitteri et al, 2008) and diet pills without a prescription, which is likely to include use of dietary supplements (Kakinami et al, 2014). Prior research has also found gender differences in the use of these products, with females more likely to use weight-loss supplements and males more likely to use musclebuilding supplements (Blanck et al, 2007;Eisenberg et al, 2012;Pillitteri et al, 2008). Though we were not able to find epidemiologic studies estimating the prevalence by gender of use of sexual-function supplements, these products are primarily marketed to men (Cui et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior research has similarly found evidence of social inequities in the burden these products pose, with two U.S. nationally representative studies finding lower-income adults more likely than their wealthier peers to use dietary supplements for weight loss (Pillitteri et al, 2008) and diet pills without a prescription, which is likely to include use of dietary supplements (Kakinami et al, 2014). Prior research has also found gender differences in the use of these products, with females more likely to use weight-loss supplements and males more likely to use musclebuilding supplements (Blanck et al, 2007;Eisenberg et al, 2012;Pillitteri et al, 2008). Though we were not able to find epidemiologic studies estimating the prevalence by gender of use of sexual-function supplements, these products are primarily marketed to men (Cui et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has also found gender differences in the use of these products, with females more likely to use weight-loss supplements and males more likely to use musclebuilding supplements (Blanck et al, 2007;Eisenberg et al, 2012;Pillitteri et al, 2008). Though we were not able to find epidemiologic studies estimating the prevalence by gender of use of sexual-function supplements, these products are primarily marketed to men (Cui et al, 2015). As might be expected, we found male-only headed households were more likely to purchase these products than other household types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Food and Drug Administration, 2017, U.S. Food and Drug Administration, 2010, Cui et al, 2015). In fact, the U.S. Food and Drug Administration has been well aware of this heightened risk for many years, and in 2010 issued a special warning to consumers regarding supplements sold for weight loss, muscle building, and sexual function as being more likely than other supplements to be deceptively marketed and tainted with toxic ingredients (U.S.…”
Section: Introductionmentioning
confidence: 99%